Availability and preferences of online references and patient medication records (PMR) facilities in community pharmacies and its impact on professional practice / Ezlina Usir - Usir, Ezlina (2010)
The study involves two surveys 1) availability and preferences of references and PMR facilities in community pharmacies and 2) importance and satisfaction of professional practice issues. In the first survey, 500 structured questionnaires were mailed to community pharmacies in a proportionally stratified random sampling manner. The questionnaire covered availability and preferences of references and PMR. In the second survey, 200 structured questionnaires were mailed to 20 community pharmacies which were stratified according to geographical region. The pharmacists then distributed this questionnaire to their patient and subsequently returned it in the provided envelope. This survey consisted of a four-point Likert scale on the importance of professional services in pharmacies and patient satisfaction and a five-point Likert scale on pharmacist’s behaviour and professionalism. The results were analyzed using SPSS 14.